Progress of Studies on Circulation Dynamics in the East China Sea: The Kuroshio Exchanges With the Shelf Currents - Liu, Zhiqiang; Gan, Jianping; Hu, Jianyu; Wu, Hui; Cai, Zhongya; Deng, Yongfei (Frontiers in Marine Science, 2021)
This study reviews recent advances in the circulation dynamics of the Kuroshio and its interaction with shelf currents in the East China Sea (ECS). The annually averaged Kuroshio volume transport varies between 19 and 24 Sv, based on different observations, but there is not consensus on the season when its volume transport peaks. The Kuroshio is intensified over the central slope of the ECS from that to the northeast of Taiwan. The total Kuroshio intrusion into the ECS shelf is estimated to be approximately 1.4 Sv, deduced from the observed volume transport of exchange flow in the Taiwan and Tsushima Straits, based on the assumption of volume conversation over the shelf. However, the uncertainty regarding to this estimation remains due to the absence of sufficient observations and understanding of the Kuroshio dynamics and its interaction with the complex slope topography. The Kuroshio intrusions over the shelf to the northeast of Taiwan and southwest of Kyushu are stimulated by planetary or topographic β-effect associated with the alongshore variation in the ECS slope topography and altered by variations in the Kuroshio intensity, shear stress, and baroclinicity. Multilayered exchanges between the Kuroshio and shelf currents were found between 100 and 200 m isobaths along the central ECS slope. The spatial variation in these exchanges is governed by cross-isobath transport by geostrophy, whereas bottom Ekman transport plays a predominant role in altering the integrated exchange flow along the slope. Although the intrusion is greatly modulated along the path of the Kuroshio off the ECS by variable slope topography, there are few observations on spatial variation of these exchange flows. The characteristics and variations in circulation and hydrographic properties of waters between 100 and 200 m isobaths significantly determine the general ECS circulation, about which consensus has still not been attained.